2015
DOI: 10.1177/0009922815580405
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors on Health-Related Quality of Life in Children With Epilepsy

Abstract: The goal of this study was to evaluate how epilepsy affected the health-related quality of life (HRQOL) in children with epilepsy, as well as the risk factors for poor HRQOL. Parents of epileptic children (n = 223) and parents of healthy children (n = 216) were enrolled. The Child Epilepsy Questionnaire-Parental form was given to all parents. Children with epilepsy had significantly lower HRQOL scores for overall QOL and all subscales. Seizure types were not associated with HRQOL, but the age of the child with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The reason had been that our society places more value on male children and so are given better healthcare for their survival and maintenance of family lineage. The observation that children with seizure disorder had significantly lower total mean scores than controls was also reported by other studies [24,25,26]. Miller et al reported that the health-related quality of life in children with seizure disorder compared with the controls is diminished in all functioning domains [24].…”
Section: Discussionsupporting
confidence: 60%
“…The reason had been that our society places more value on male children and so are given better healthcare for their survival and maintenance of family lineage. The observation that children with seizure disorder had significantly lower total mean scores than controls was also reported by other studies [24,25,26]. Miller et al reported that the health-related quality of life in children with seizure disorder compared with the controls is diminished in all functioning domains [24].…”
Section: Discussionsupporting
confidence: 60%
“…While some studies revealed relatively good QOL measures in both children and parents (Ferro et al, 2017), a systematic review revealed that parents of children with epilepsy had a reduced quality of life, similar to parents of children with other chronic conditions; mothers were more affected than fathers (Puka et al, 2018). QOL was inversely associated with socioeconomical status, anxiety and depression, but seemed not to be correlated with the child's seizure frequency (Ferro et al, 2017;Puka et al, 2018), although a recent study found that children with higher seizure frequency and younger age at onset presented with lower QOL scores (Liu et al, 2015). The main reported determinants of both felt stigma and QOL are summarized in table 2.…”
Section: Cultural Aspects and Consequences Of Diagnosismentioning
confidence: 99%
“…These three clinical factors suggested that specific features can identify children at high risk of poor healthrelated QOL. 20 No statistical significance was found in difference of QOL in children with focal epilepsy and the presence of epileptic syndrome. This may be a sign that children and parents are not much concerned about the severity or type of epilepsy, but taking more drugs or having frequent seizures has a more negative impact on QOL.…”
Section: Discussionmentioning
confidence: 95%